On Horseback - Warner, Charles Dudley, 1829-1900 (Salt Lake City, UT : Project Gutenberg, 2004)
"On Horseback" by Charles Dudley Warner is a travel narrative likely written during the late 19th century. The book chronicles the adventures of a Professor and his companion, the Friend of Humanity, as they embark on an exploration of the countryside in Virginia and parts of North Carolina, primarily focusing on life, landscape, and the characters they meet along their journey. The opening of "On Horseback" introduces readers to the Professor and the Friend of Humanity as they prepare for their trip. They are depicted with a humorous tone, engaging in a discussion about horsemanship while preparing to saddle their horses outside a hotel in Abingdon, Virginia. The narrative paints a vivid picture of the region, describing the sights, sounds, and the leisurely atmosphere post-Civil War, filled with local color and idiosyncratic characters. As they set off South, the duo's lighthearted debates and observations set the stage for a journey rich in natural beauty and regional quirks, marked by an easy-going exploration into the life of the people they encounter, highlighting both the charm and challenges faced in post-war Southern America. (This is an automatically generated summary.)
Release date is 2004-10-10
Produced by David Widger
Keywords: California -- Description and travel; Virginia -- Description and travel; North Carolina -- Description and travel; Tennessee -- Description and travel; Mexico -- Description and travel; Warner, Charles Dudley, 1829-1900 -- Travel -- Southern States; Appalachian Region -- Description and travel; Warner, Charles Dudley, 1829-1900 -- Travel -- Appalachian Region; Warner, Charles Dudley, 1829-1900 -- Travel -- Mexico